Numerical simulation on the migration and deposition of micron-sized sand particles in the helical tube section during hydrate production tests - Yinao Su; Ye Chen; Xiaofeng Sun; Tie Yan; Jingyu Qu; Ruixi Duan (Natural Gas Industry B, 2020)
In the exploitation process of offshore natural gas hydrate (“hydrate” for short), it is necessary to take into consideration the wear of wellbore equipment caused by micron-sized sand particles after their breaking through the sand control facility of the wellbore. At present, however, there is no literature on the migration, deposition and blockage of micron-sized sand particles (<44 μm) after their flowing into the wellbore with the formation fluid. To deal with this situation, this paper took the sand particles in a throttling helical tube section for water transport in the process of depressurization hydrate exploitation as the research object. After a geometric model of flow channel was established for numerical simulation, the migration and deposition laws of micron-sized sand particles were analyzed and the critical non-deposition water velocity of micron-sized sand particles under different conditions was obtained. And the following research results were obtained. First, micron-sized sand particles are mainly accumulated in the helical tube section of a complex pipeline, and the deposition of sand particles decreases with the increase of water velocity. The sand particles deposited in the upper part of the helical tube section are more difficult to clean than those in the lower part. Second, the critical non-deposition water velocity increases gradually with the increase of sand particle size and sand production concentration. Third, the variables are nondimensionalized by applying the Buckingham-Π theorem. And the model for predicting the sand deposition concentration in the local complex wellbore section during hydrate production test can be obtained using the OriginPro 2019 non-linear fitting tool. Fourth, based on the proposed concept of sand deposition concentration ratio, combined with the deposition prediction model, it is convenient to calculate critical non-deposition water velocity of micron-sized sand particles and to judge the situation of sand deposition in the wellbore. In conclusion, a method for determining the critical non-deposition water velocity of micron-sized sand particles in the local complex wellbore section during the hydrate production test is proposed. And by virtue of this method, the critical non-deposition water velocity of micron-sized sand particles under three particle sizes and three sand production concentrations is obtained respectively. And the research results provide a basis for the reasonable arrangement of hydrate production system and pressure reduction range.